Diorganotin(IV) carboxylates of 3-methylphenyl ethanoic acid: Synthesis, crystal structure, antibacterial, anticancer and molecular docking studies. (2nd November 2019) - Muhammad, Niaz; Ali, Saqib; Nawaz Tahir, Muhammad; Shujah, Shaukat; Wadood, Abdul; Khan, Huma
Abstract: Di- n -butyl- (1 ) and diethyltin(IV) (2 ) derivatives of 3-methylphenylethanoic acid were synthesized and characterized by elemental analysis, atomic absorption, IR, 1 H and 13C NMR spectroscopy and mass spectrometry. The spectroscopic data and single crystal X-ray diffraction studies for complex2 have confirmed a bidentate coordination mode of the carboxylate ligand and the presence of hexacoordinated tin atoms in the complexes. The complexes were screened for their in vitro antibacterial activity against selected gram positive and gram negative bacterial strains. The anticancer potential was assessed against prostate cancer cell lines. Both complexes have shown higher activities than the ligand acid. Complex1 with an IC50 value of 4.97 ± 0.27 μg/mL was found to be better anti prostate cancer agent than complex2 (IC50 = 11.26 ± 2.18 μg/mL). Molecular docking study has suggested antibacterial action of the complexes in terms of their ability to develop hydrogen bonding and hydrophobic interactions with vital residues of the target proteins like tyrosyl-tRNA synthase from Staphylococcus aureus (gram-positive bacteria) and undecaprenyl diphosphate synthase from Escherichia coli (gram-negative bacteria). Graphical Abstract: